Aplikasi teknologi pembuatan pembenah tanah dari limbah penyulingan sereh (Cymbopogon citratus) - Wahjuni Hartati; Triyono Sudarmadji; Syahrinudin; Muhammad Oky Pratama Septiaji Putra (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2022)
The purpose of the activity is to motivate and equip the community to utilize the solid waste of Cymbopogon citratus distillation of lemongrass as raw material for making soil improvers. The benefit of the activity in general is that it provides information on alternative sources of raw materials for making soil improver in handling degraded land in East Kalimantan which is quite extensive and provides alternative business opportunities for developing the soil improver manufacturing industry. The benefits of this activity in particular are to prevent soil quality degradation by returning organic matter in situ to the original environment. Activities are carried out offline/face to face with strict health protocols. The method used is counseling/discussion lectures followed by the practice of making bokashi soil improvers and POCs made from solid waste from citronella leaf oil distillation using EM-4 activator and tape yeast. The participants of the activity were 30 people consisting of 14 participants who were residents of RT 19, Mugirejo Samarinda Village, the rest were UNMUL Fahutan students who were carrying out activities in the village. Bokashi and POC were successfully harvested after 5 (five) days.